THE THEORETICAL FRAMEWORK OF THE THEORY OF CIVIL RESPONSIBILITY - Dr. Bakhit Mohd AlDajeh, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Civil responsibility occupies an important, prestigious and sensitive position in the legal system, specifically in the philosophy of civil law. Civil liability gives an Individuals the rights to obtain compensation if he/she suffer from the wrong act of other Individuals by suing them. Therefore, to be an awarded of compensation, the injured party has to have suffered an actual loss, such as; damage to property or financial loss. Nowadays, there is doubt that that civil responsibility is unable to keep up with new developments of life. This research aims to identify the theoretical aspects of the theory of civil liability. Furthermore, this research also aims to clarify what is meant by both contractual liability and omissive responsibility, what is the difference between them using the approach of juridical-normative with descriptive analysis This study has reach to a result that omissive responsibility and contractual responsibility are differ if we address their original source of obligation, but both responsibility are based on the general and legal obligation of not harming others in the society. Even if their original source of obligation is not the same there is a very great convergence in nature between both of it. Considering this, it is necessary to consider the possibility of establishing a legal system that is independent of the traditional one that would avoid the constraints and challenges of that responsibility.